Designing a Multi-Objective Stable Mathematical Model for Routing Municipal Waste Collection Vehicles - Afrouz Rahmandoust; Ashkan Hafezalkotob; Bijan Rahmani Parchikolaei; َAmir Azizi (مدیریت صنعتی)
Objective Waste collection poses a significant challenge for contemporary societies. Given the inevitability of ongoing human waste production, the organization of municipal waste collection holds paramount importance. Against the backdrop of escalating environmental pollutants over recent decades and crises induced by global warming, governments have increasingly prioritized addressing sustainability issues. The objective of this study was to formulate an urban waste collection network with a municipal sustainability perspective. To achieve this goal, we proposed a multi-objective mathematical model that incorporates economic, social, and environmental considerations pertaining to the routing of urban waste collection vehicles.